Заметки о Tetrops starki (Coleoptera, Cerambycidae, Tetropini) - Мирошников, А.И. (Вестник зоологии, 1993)
The interesting findings of scantily studied species of longicorn beetles of the USSR fauna — Tetrops starki C h e v r.— are given. Some peculiarities of its ecology are recorded. It is shown, that in the North-Western Caucasus (in Krasnodar environments) populations of this species consist only of specimens possessing blalk elytra with broad brown and someti/mes yel-low-brown brand along suture, while typical coloration of elytra of this species in different. It has been determined, that another species of genus- T. praeusla (L.), being found at the same locality that T. starki, possesses various coloration of elytra (from entirely yellow to black), even within specimens, reared from neighbouring branches of the same free. Data on parasites of larvae of T. starki (from fam. Braconidae) are given.